2012
DOI: 10.1002/stem.1151
|View full text |Cite
|
Sign up to set email alerts
|

Stable Long-Term Blood Formation by Stem Cells in Murine Steady-State Hematopoiesis

Abstract: Hematopoietic stem cells (HSCs) generate all mature blood cells during the whole lifespan of an individual. However, the clonal contribution of individual HSC and progenitor cells in steady‐state hematopoiesis is poorly understood. To investigate the activity of HSCs under steady‐state conditions, murine HSC and progenitor cells were genetically marked in vivo by integrating lentiviral vectors (LVs) encoding green fluorescent protein (GFP). Hematopoietic contribution of individual marked clones was monitored b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
2
6
0
Order By: Relevance
“…Stochastically, a fraction of these clones can get recruited for blood production, where they undergo commitment and a massive proliferative burst to produce detectable PB progeny. Our findings of successive and polyclonal long-term behaviour are supported by irradiation marking experiments 27,28 and by more recent studies involving in vivo lentiviral tagging 29 . Similarly, variance analyses have predicted that haematopoiesis is maintained by a large number of haematopoietic clones 30,31 .…”
Section: Discussionsupporting
confidence: 85%
“…Stochastically, a fraction of these clones can get recruited for blood production, where they undergo commitment and a massive proliferative burst to produce detectable PB progeny. Our findings of successive and polyclonal long-term behaviour are supported by irradiation marking experiments 27,28 and by more recent studies involving in vivo lentiviral tagging 29 . Similarly, variance analyses have predicted that haematopoiesis is maintained by a large number of haematopoietic clones 30,31 .…”
Section: Discussionsupporting
confidence: 85%
“…A competitive mouse bone marrow transplantation (BMT) study was chosen to test whether hdCK3mut can detect transplanted cells during early hematopoietic reconstitution (24)(25)(26)(27)(28). Donor cells were generated by treating mice with 5-flourouracil 5 d preharvest for HSC enrichment.…”
Section: Expression Of Hdck3mut In Mouse Hscs Allow Noninvasive Detecmentioning
confidence: 99%
“…We examined whether reporter cells in BMT-recipient mice retained the PET reporter function through serial imaging in vivo. Consecutive scans and peripheral blood analysis were obtained at 4, 15, 27, and 32 wk post-BMT allowing for detection of both short-and long-lived reporter HSCs (27,28).…”
Section: Reporter Labeled Mouse Hscs Retain Expression Of Hdck3mut Withmentioning
confidence: 99%
“…However, several experimental findings have indicated a more complex organization of the immature hematopoietic cells and also challenged the idea that the extensive self-renewal capacity is a unique property of HSCs (Adolfsson et al, 2005;England et al, 2011;Yamamoto et al, 2013;Kim et al, 2015). It was also demonstrated that the undisturbed murine hematopoiesis is maintained by multiple clones acting in parallel (Zavidij et al, 2012;Sun et al, 2014) without any significant contribution from HSCs. Busch et al (2015) also demonstrated that undisturbed adult hematopoiesis is largely sustained by cells downstream of HSCs, and Schoedel et al (2016) reported a long-term hematopoiesis occurring in the absence of HSCs while, in contrast, Sawai et al (2016) and Akinduro et al (2018) presented the data supporting the continuous contribution of HSCs for steady state hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%